"We're not only here but we're there in spirit": Asymmetrical mobile intimacy and the transnational Filipino family. (January 2018) - Cabalquinto, Earvin Charles B.
Organising, performing, and experiencing festive family rituals sustain relationships among family members. However, in recent times, high levels of human migration alongside the rapid development of digital communication technologies are reconfiguring family traditions. This paper investigates the ways in which 21 overseas Filipino workers in Melbourne, Australia, and their left-behind family members in the Philippines use mobile devices and communications platforms to restage festive family rituals. Employing a visual method and drawing on in-depth interviews, the empirical study uncovers the personalised and heterogenous practices of the transnational Filipino family in performing intimacy at a distance, paving the way for constructing copresence during festivities. Importantly, using the mobilities lens (Urry, 2007) as a framework for critical investigation, the findings show that a disproportionate level of network capital as informed by age, gender, and social class produces "asymmetrical mobile intimacy." The present study also reveals how ambivalent feelings emerge due to technological asymmetries and parameters. Importantly, transnational families often negotiate such contradictory experiences through mobile device use. By comparing and contrasting the mobile practices of dispersed family members, the present study uncovers the hidden social inequalities perpetuated in a networked family life.